The Embedded Firm: Corporate Governance, Labor, and Finance Capitalism - Williams, Cynthia A.; Zumbansen, Peer (Cambridge University Press, 2011)
The globalization of capital markets since the 1980s has been accompanied by a vigorous debate over the convergence of corporate governance standards around the world towards the shareholder model. But even before the financial and economic crisis of 2008/2009, the dominance of the shareholder model was challenged with regard to persisting divergences and national differences in corporate law, labor law and industrial relations. This collection explores this debate at an important crossroads, echoing Karl Polanyi's famous observation in 1944 of the disembeddedness of the market from society. Drawing on pertinent insights from scholars, practitioners and regulators in corporate and labor law, securities regulation as well as economic sociology and management theory, the contributions shed important light on the empirical effects on the economy of the shift to shareholder primacy, in light of a comprehensive reconsideration of the global context, policy goals and regulatory forms which characterize market governance today.
Keywords: business & economics / management; corporate governance; disembeddedness; international law; political science / public policy / economic policy

Grounding Globalization: Labour in the Age of Insecurity - Webster, Edward; Lambert, Rob; Beziudenhout, Andries (John Wiley & Sons, 2011)
*Winner of the 2009 Distinguished Scholarly Monograph Prize, awarded by the American Sociological Association Labor and Labor Movements section* Claims have been made on the emergence of a new labour internationalism in response to the growing insecurity created by globalization. However, when persons face conditions of insecurity they often turn inwards. The book contains a warning and a sign of hope. Some workers become fatalistic, even xenophobic. Others are attempting to globalize their own struggles. Examines the claim that a new labour internationalism is emerging by grounding the book in evidence, rather than assertion Analyzes three distinct places – Orange, Australia; Changwon, South Korea; and Ezakheni, South Africa – and how they dealt with manufacturing plants undergoing restructuring Explores worker responses to rising levels of insecurity and examines preconditions for the emergence of counter-movements to such insecurities Highlights the significance of 'place' and 'scale', and demonstrates how the restructuring of multi-national corporations, and worker responses to this, connect the two concepts
Keywords: Polanyi problem; critique; globalization; internationalism; labour; science / earth sciences / geography

Economic Anthropology - Hann, Chris; Hart, Keith (Polity, 2011)
This book is a new introduction to the history and practice of economic anthropology by two leading authors in the field. They show that anthropologists have contributed to understanding the three great questions of modern economic history: development, socialism and one-world capitalism. In doing so, they connect economic anthropology to its roots in Western philosophy, social theory and world history. Up to the Second World War anthropologists tried and failed to interest economists in their exotic findings. They then launched a vigorous debate over whether an approach taken from economics was appropriate to the study of non-industrial economies. Since the 1970s, they have developed a critique of capitalism based on studying it at home as well as abroad. The authors aim to rejuvenate economic anthropology as a humanistic project at a time when the global financial crisis has undermined confidence in free market economics. They argue for the continued relevance of predecessors such as Marcel Mauss and Karl Polanyi, while offering an incisive review of recent work in this field. Economic Anthropology is an excellent introduction for social science students at all levels, and it presents general readers with a challenging perspective on the world economy today.Selected by Choice as a 2013 Outstanding Academic Title
Keywords: cultural anthropology; economic anthropology; social anthropology; sociology - general

Understanding India’s New Political Economy: A Great Transformation? - Ruparelia, Sanjay; Reddy, Sanjay; Harriss, John; Corbridge, Stuart (Taylor & Francis, 2011)
A number of large-scale transformations have shaped the economy, polity and society of India over the past quarter century. This book provides a detailed account of three that are of particular importance: the advent of liberal economic reform, the ascendance of Hindu cultural nationalism, and the empowerment of historically subordinate classes through popular democratic mobilizations. Filling a gap in existing literature, the book goes beyond looking at the transformations in isolation, managing to: • Explain the empirical linkages between these three phenomena • Provide an account that integrates the insights of separate disciplinary perspectives • Explain their distinct but possibly related causes and the likely consequences of these central transformations taken together By seeking to explain the causal relationships between these central transformations through a coordinated conversation across different disciplines, the dynamics of India’s new political economy are captured. Chapters focus on the political, economic and social aspects of India in their current and historical context. The contributors use new empirical research to discuss how India’s multidimensional story of economic growth, social welfare and democratic deepening is likely to develop. This is an essential text for students and researchers of India's political economy and the growth economies of Asia.
Keywords: India; business & economics; ethnic studies

Il sofisma economicista: intorno a Karl Polanyi - Caillé, Alain (sn, 2011)
KM translate: "The economic sophistry" and "The two meanings of" economic "", short writings by Karl Polanyi published here partially in a version taken from the French magazine MAUSS, represent a wonderful example of critical synthesis and set of depth of analysis, an analysis that comes to the conviction of the anthropological and social disaster caused not only by liberalism, but even more by the fallacy of an entire system of thought, economic science, which seeks to justify and support it. In support of the interesting pages of Polanyi, this book presents two contributions, respectively by Alain Caillé with Jean-Louis Laville and Jerome Maucourant, which, in addition to quickly presenting the intellectual biography of the Hungarian philosopher, clarify the extreme relevance of his critique of capitalism and the society of the markets. Polanyi emerges as an economist from the solid historical and anthropological foundations that, with his work, has been able to dismantle the apparently solid building of the classical economy to reveal its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century.
Keywords: business & economics; economic theory

Karl Polanyi, Globalisation and the Potential of Law in Transnational Markets - Joerges, Christian; Falke, Josef (Hart, 2011)
The patterns and impact of globalization have become a common concern of all international jurists, sociologists, political scientists, and philosophers. Many have observed the erosion of the powers of nation states and the emergence of new transnational governance regimes, and seek to understand their internal dynamics, re-regulatory potential, and normative quality. Karl Polanyi's seminal book - The Great Transformation - is attracting new attention to such endeavors, mirroring a growing sensitivity to the social and economic risks of dis-embedding politics. Their re-construction by Polanyi - including his warning against a commodification of labor, land, and money - provide the trans-disciplinary reference point for the contributions to this book. Political economy, political theory, sociology, and political science inform this discussion of Polanyi's insights in the age of globalization. Further theoretical essays and case studies look at his 'false commodities': money, labor (and services), and land (and the environment). Jurists have hardly ever discussed Polanyi, and the law has not been taken very seriously among 'Polanyians.' It is nevertheless clear that economic stability and social protection are simply inconceivable without the visible hand of law. The legal discussion in this book's concluding chapters do not, and cannot, depart directly from such premises. The framework of their analyses is, instead, informed by current debates on the emergence of para-legal regimes, the fragmentation of international law, and the prospects of constitutional perspectives within which the rule of law and the notion of law-mediated legitimate governance are established. Polanyi's notion of the co-originality of dis-embedding moves and re-imbedding countermoves can, however, be usefully employed in the re-construction of the sociological background of the moves and tensions which jurists discern.
Keywords: conflict of laws; jurisprudence; law - commercial; political science - history and theory